API-Led Connectivity for SAP S/4HANA: Unlocking Business Value through Reusable Services (Global Journal of Computer Science and Technology, 2025)
Organizations face mounting pressures to extract maximum value from SAP S 4HANA investments while maintaining market flexibility This article presents API-led connectivity as a strategic catalyst transforming enterprise integration through layered architecture-system process and experience APIs-where business functions become reusable services System APIs reveal critical company information while process APIs manage intricate business tasks and experience APIs shape output for different user needs Keeping these connections secure requires strict access rules layered safeguards and proper data handling practices Effective governance tools help companies monitor usage and scale connections across business partners Factory operations flow more efficiently retail stores connect online and in-person shopping effortlessly and financial institutions bring new capabilities to market with less delay creating competitive edges reducing expenses and building stronger customer relationships Companies can respond to changing business conditions without endangering essential operations elevating S 4HANA beyond basic accounting into a platform that drives business advancement and fresh opportunities
Keywords: API-led connectivity; SAP S/4HANA integration; micro services architecture; security framework; digital transformation